2004
DOI: 10.1038/sj.onc.1208048
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of apoptosis by fau revealed by functional expression cloning and antisense expression

Abstract: Functional expression cloning is a powerful strategy for identifying critical steps in biological pathways independently of prior assumptions. It is particularly suitable for the identification of molecules crucial to the control of apoptosis. Our screen for sequences suppressing T-cell apoptosis isolated a sequence antisense to fau (FinkelBiskis-Reilly murine sarcoma virus (FBR-MuSV)-associated ubiquitously expressed gene). The fox gene in FBR murine osteosarcoma virus is also antisense to fau and several rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 57 publications
(50 reference statements)
5
31
0
Order By: Relevance
“…Although the potential for FAU itself to act as a target to increase chemotherapy-induced cell death is limited since it is ubiquitously expressed in different human tissues (Mourtada-Maarabouni et al, 2004), potential targets down-stream of FAU, particularly the BCL2-family member BCL-G (which is also controlled by maternal embryonic leucine zipper kinase (MELK)), may well prove amenable to the development of novel therapies. BCL-G is a proapoptotic protein (Guo et al, 2001), which has been implicated in the activation of T-cells (Nakamura and Tanigawa, 2003) and has been shown to be significantly downregulated in prostate cancer compared with normal prostate tissue (Kibel et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the potential for FAU itself to act as a target to increase chemotherapy-induced cell death is limited since it is ubiquitously expressed in different human tissues (Mourtada-Maarabouni et al, 2004), potential targets down-stream of FAU, particularly the BCL2-family member BCL-G (which is also controlled by maternal embryonic leucine zipper kinase (MELK)), may well prove amenable to the development of novel therapies. BCL-G is a proapoptotic protein (Guo et al, 2001), which has been implicated in the activation of T-cells (Nakamura and Tanigawa, 2003) and has been shown to be significantly downregulated in prostate cancer compared with normal prostate tissue (Kibel et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The gene FAU (Finkel-Biskis-Reilly murine sarcoma virus (FBR-MuSV)-associated ubiquitously expressed gene) was recently identified as a novel regulator of apoptosis by this approach (Rossman and Wang, 1999;MourtadaMaarabouni et al, 2004). Mourtada-Maarabouni et al, (2004) further demonstrated that downregulation of FAU expression in a murine lymphocyte cell line induced resistance to apoptosis induction by a range of treatments, including cisplatin. Indeed independent evidence suggests that FAU may act as a tumor suppressor gene , and its expression has been shown to be down-regulated in breast cancer (Abba et al, 2004;Pickard et al, 2009).…”
Section: Introductionmentioning
confidence: 93%
“…Expression of fau is down-regulated in both breast cancer (Pickard et al, 2009) and ovarian cancer (Moss et al, 2010). A sequence antisense to fau is able to inhibit apoptosis (AP) induced by dexamethasone, UV or cisplatin in W7.2c cells (Mourtada-Maarabouni et al, 2004). FAU was also found to regulate apoptosis in human T-cell lines and HEK293/17 cells (Pickard et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Functional cloning and retroviral cDNA libraries have been applied to define genes responsible for drug resistance, apoptosis, and so forth (Perez-Victoria et al, 2003;Mourtada-Maarabouni et al, 2004). In identifying genes related to cisplatin resistance, the approaches that have been used have a major drawback because of continuous stepwise challenge with increased cisplatin concentrations and may reflect secondary changes in genotype and phenotype during multistep selection of cisplatin-resistant cells.…”
mentioning
confidence: 99%